APPLICATION OF THE METHOD OF COMPARATIVE STUDIES STUDY OF HISTORICAL AND PEDAGOGICAL INFORMATION - Sadova, V.V. (Pedagogy of Higher and Secondary Education, 2009)
The article reveals some possibilites for the concept of comparison science use as the methodological background of history-and-pedagogy researches.